Examining Female Entrepreneurs' Management Style: An Application of a Relational Frame - Buttner, E. Holly (Journal of business ethics, 2001)
This paper reports the results of a qualitative analysis of female entrepreneurs' accounts of their role in their organizations using Relational Theory as the analytical frame. Content analysis of focus group comments indicated that the women used a relational approach in working with employees and clients. Relational skills included preserving, mutual empowering, achieving, and creating team. Findings demonstrate that Relational Theory is a useful frame for identifying and explicating women entrepreneurs' interactive style in their own businesses. Implications and future directions for research are discussed.